Returning to the scene of the trauma in PTSD treatment – why, how and when?. (9th November 2015) - Murray, Hannah; Merritt, Christopher; Grey, Nick
Abstract: Returning to the scene of the trauma is often recommended as part of trauma-focused cognitive-behavioural therapies for post-traumatic stress disorder (PTSD). Many clinicians avoid site visits due to lack of confidence or practical constraints; however, recent research suggests this is a valuable part of treatment. This article summarizes a rationale for including the site visit as part of cognitive therapy for PTSD, as well as the main considerations about when to carry it out in treatment. A practical framework for planning and implementing site visits is described.